MUSICAL TRAINING EXPERIENCE IN A PRIVATE UNIVERSITY IN LIMA - Ravelo Franco, Daniel (2012)
The aim of the Musical Training Revolution is to take advantage of the modern educational technology tools, to apply them to the auditory training in a professional music training program. In this paper, the experience of transforming the classroom course in Leveling in Reading and Ear Training is presented, from a university undergraduate Music, to a b-learning mode. b-learning mode of this course is set on a virtual classroom on the Moodle platform. Online work within this virtual classroom included communication forums, academic forums, ear training self-instructive resources and academic tasks. The working strategy of on-line courses considered several aspects: 1) Structure of the virtual classroom. 2) Communication within the virtual classroom. 3) Managing the virtual classroom. 4) Create and organize content. 5) Provide an online study methodology. 6) Design and implementation of online activities. 7) Rate of online activities. 8) Evaluation of the whole process. The results of this experience forced us to rethink the contents of the same course at the following levels due to the substantial progress made.